The revival of transcendental thought in the writings of gary snyder, wendell berry and annie dillard / Firas A. Nsaif - Firas, A. Nsaif (2016)
The transcendentalist movement had a huge influence on literary and cultural circles in nineteenth century America but witnessed a severe decline in the last decades of the nineteenth century and the first half of the twentieth century due to an anti-idealist mood that grew to dominate society. This study deals with three contemporary American writers, Gary Snyder, Wendell Berry and Annie Dillard, whose writings have given new life to transcendental thought. In this thesis, I argue that these writers revived transcendental values to deal with contemporary American and worldwide ecological, social and spiritual issues. To be specific, these transcendental values deal with the harmonious relationship between man and nature, the rejection of modern society's materialism and the assertion of individual freedom along with the call for the adoption of an authentic relationship with God which goes beyond organized religion. They found a cure for the diseases of modern civilization in these transcendental ideals. Snyder, Dillard and Berry’s writings represent a link between transcendentalism and ecology since their ecological-oriented writings embody their interest in transcendental principles within new eco-approaches to literature that inherit and develop transcendentalism fundamentals concerning an individual’s relation to society, God and the natural world. This study is based on thematic units and does not deal with each writer separately. Chapter One provides a background on Transcendentalism and its founding fathers, Ralph Waldo Emerson and H.D. Thoreau in addition to a background of the twentieth-century ecology movement and ecocriticism. ChapterTwo explores the ecological visions of the three writers and how they embody transcendental values through an analysis of the writers’ selected poetic and prose works. Gary Snyder’s ecological vision, considerably derived from Buddism, emphasizes the coexistence and equality of humans and living and non-living beings. Wendell Berry is less radical than Snyder; he supports farm life simplicity rather than a primitive life and calls for a reconciliation between the farm and the wilderness. Annie Dillard meditates on the contradictions in the natural world as she realizes that beauty and violence complete each other and cannot be separated. It is the rule of the wild, according to Dillard, and should be accepted by people. Chapter Three deals with the social implications of Transcendentalism in the works of the three writers. Berry dignifies physical work and presents an ideal image of farm-town unity. To him, fidelity to the land is true citizenship. Snyder’s vision of an ideal political world is basically based on bioregionalist attitudes. Snyder also calls for a new kind of democracy that is not limited to human beings but shared by all living beings and it is only through this democracy that the earth can survive and be preserved. Dillard hardly touches on social issues directly but does elevate the position of the human condition in society. In the heroine of her novel Maytrees, she embodies the Emersonian concept of self-reliance as a way of preserving consistency in society. Chapter Four deals with spiritual and religious matters in the works of Snyder, Berry, and Dillard. Snyder draws considerably from Buddhist ideals in his spiritual vision while Berry presents a new vision of Christianity and an agrarian approach that leads towards a mystical life. Dillard's spiritual vision is Christian but her use of scientific methods gives her spirituality a scientific dimension.